Evaluation Of Performance Assessment Based On The Digital Asn Application At The Energy And Mineral Resources Agency Of Lampung Province - Ulyyanti, Riska; Dunan, Hendri (Cita konsultindo, 2026)
This study aims to evaluate the implementation of ASN performance assessments based on the Digital ASN Application at the Energy and Mineral Resources Office of Lampung Province, as well as to assess the understanding of ASN and the effectiveness of its application. The study uses an evaluative descriptive qualitative approach with data collection techniques through interviews, observations, and documentation. Data analysis is conducted using the CIPP evaluation model (Context, Input, Process, Product). The results of the study indicate that the Digital ASN Application has been implemented in accordance with regulations and is able to improve transparency and administrative efficiency in performance assessments. However, its use is still administrative in nature and not yet optimal as a strategic performance management tool due to limitations in training, variations in civil servants' capabilities, and the misalignment of performance indicators with organizational goals. This study concludes that optimizing the application requires strengthening civil servants' competencies, refining performance indicators, and leadership support to sustainably improve civil servants' performance.